Autonomia da luz: um estudo das obras de Mirella Brandi x MuepEtmo e Luiz duVa - Poser, Victória Boni Von (2017)
This academic work is devoloped from the debate of light as an artistic autonomous language in contemporary art and ponders over the questions that this autonomy proposes. To introduce this debate a bibliographical research was made concerning light in visual arts, across different historical periods, within the interdisciplinary scope in which the technologies and languages are approached. However, the investigation in this dissertation is focused on the study of the experiences and works by renowned and active artists in the contemporary Brazilian scene: the duo Mirella Brandi x MuepEtmo and the artist Luiz duVa. The research presented here involves these contemporary artist’s critical fortune, along with unpublished interviews with the three artists during the year of 2016 and the first semester of 2017. To show the autonomy of light in their artworks, readings of the Trilogia das Cores (Color Trilogy 2010-2015), light and sound performances by the duo Mirella Brandi x MuepEtmo that research the narrative potential of these elements, along with the luminous installation Espaço Alter[ado] (Alter[ade] Space 2014-2015) and the live experiences PULSAR (PULSATE 2014-2015) by Luiz duVa were conducted. In the final considerations, this academic work shows that the light perceived and worked by the artists has an autonomous character, because it can be considered as the main element in their work. It is also believed that the light in their works sparks the debate on the issues such as narrative, materiality, the spectator’s perception and the challenges in the documentation.